2016
DOI: 10.1177/1040638716632815
|View full text |Cite
|
Sign up to set email alerts
|

Detection of pregnancy-associated glycoproteins in milk and blood as a test for early pregnancy in dairy cows

Abstract: Abstract. The objective of our study was to evaluate 2 pregnancy-associated glycoprotein (PAG)-based enzyme-linked immunosorbent assays (ELISAs) for use with either blood or milk. From 12 dairy farms, 116 Montbéliarde or Holstein cows were selected that had either undergone artificial insemination (AI; n = 102) or had calved (n = 14) 2-3 months earlier and had not undergone any further AI. Serum, plasma, and milk were obtained from all cows; serum and plasma were analyzed using the blood pregnancy test and mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 23 publications
(34 reference statements)
6
21
0
1
Order By: Relevance
“…The sensitivity of the commercial milk ELISA has been estimated to range between 98% and 100% for cows >30 days of pregnancy. Specificity of this milk assay was estimated to range between 83% and 100% in these same studies (Leblanc, 2013;Lawson et al, 2014;Ricci et al, 2015;Commun et al, 2016). The specificity of the milk ELISA was estimated to be lower than the corresponding estimates for the serum ELISA (when both performed in the same study), which is similar to what was found in the present study.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The sensitivity of the commercial milk ELISA has been estimated to range between 98% and 100% for cows >30 days of pregnancy. Specificity of this milk assay was estimated to range between 83% and 100% in these same studies (Leblanc, 2013;Lawson et al, 2014;Ricci et al, 2015;Commun et al, 2016). The specificity of the milk ELISA was estimated to be lower than the corresponding estimates for the serum ELISA (when both performed in the same study), which is similar to what was found in the present study.…”
Section: Discussionsupporting
confidence: 85%
“…The sensitivity of this quantitative commercial serum ELISA has been estimated to be between 98.4% and 100% for cows >30 days of pregnancy. Within the same studies, specificity was estimated to range between 88.6% and 100% (Ricci et al, 2015;Commun et al, 2016). The sensitivity of the commercial milk ELISA has been estimated to range between 98% and 100% for cows >30 days of pregnancy.…”
Section: Discussionmentioning
confidence: 91%
“…PAG glycoproteins are one major group of the proteins secreted from trophoblast cells of the placenta into the maternal blood shortly after implantation and are detectable throughout gestation [ 56 ]. These proteins have been used to monitor embryonic viability as biochemical pregnancy markers in the cow’s blood or milk [ 75 ] as well as placental functions in cattle [ 76 , 77 ]. Significant reductions in PAG concentrations during the late embryonic/early fetal period are associated with pregnancy failures in cattle [ 76 , 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy-associated glycoproteins (PAG) are secreted by the trophoblast cells of the placenta and are detectable in the maternal circulation around the time of attachment of the fetal placenta (3rd week in cattle), as well as in blood and milk throughout gestation (Zoli et al, 1992b;Friedrich and Holtz, 2010;Commun et al, 2016). The function of PAG is largely unclear; however, some studies have indicated a potential role in placental development, pregnancy maintenance, embryo survival, proteolytic activity, and immune modulation (Dosogne et al, 2002;Telugu et al, 2010;Pohler et al, 2013).…”
Section: Introductionmentioning
confidence: 99%